Contraction of range, declines in abundance and site-based threats to Velvet Scoter Melanitta fusca breeding in the Caucasus - Özkoç, Ömral Ü.; Paposhvili, Nika; Aghababyan, Karen; Petersen, Ib K.; Fox, Anthony D. (Wildfowl, 2025)
The geographically discrete Caucasus breeding population of the Velvet Scoter Melanitta fusca has shown significant range contraction to its one last existing colony in Georgia. Despite active conservation efforts at this site, where numbers currently appear to be stable, there is an evident need to understand past and present pressures that have driven the species to the verge of extinction in the region. An assessment of the potential for recreating suitable conditions for restoring the species to its former range and abundance is also required. Here, we review historical information to determine potential factors (some of which may still be in place) that contributed to the decline and range contraction of the Velvet Scoter in Armenia, Georgia and Türkiye. Breeding surveys conducted in all three countries since 2013 confirmed the species’ absence from all sites except for the breeding colony at Lake Tabatskuri in Georgia, which supported 45–50 pairs in 2024. Of 13 lakes with documented observations of Velvet Scoters, seven were confirmed as former breeding sites, with < 150 pairs in the last 60 years. The remainder were either spring/autumn staging areas, or unconfirmed breeding sites. For some sites, reasons for the loss of breeding Velvet Scoter locally were evident; for instance, at Lake Sevan in Armenia, reductions in the water levels in the lake rendered nesting islands accessible to terrestrial predators. Elsewhere, it was not possible to identify the causes of declines and extinctions, but by using the IUCN-CMP classification of threats and stresses we identified interactions with native species, recreational activity, hunting/egg collecting and fishing as critical threats to the viability of Velvet Scoters in the Caucasus. Several sites are suffering water quality issues, which require management interventions to restore turbid water to clear aquatic systems before the sites would become suitable for the return of the species. More site-based research and management will be necessary to restore the Velvet Scoter to its former levels of abundance and distribution.